Penerapan Etika Bisnis Islam Dalam Usaha Meubel Kayu: (Studi Pada Meubel Kayu Unit 1 Aimas, Kabupaten Sorong) - Nur Faizah; Maya Puspita Sari (Prodi Ekonomi Syariah IAIN Sorong, 2021)
This study discusses the application of Islamic business ethics in the wood furniture business. Study on Wood Furniture Unit 1 Aimas, Sorong Regency, the purpose of this study is to find out how the application of Islamic business ethics in the wood furniture business. Qualitative descriptive research is intended to obtain a good, clear picture and can provide data as accurately as possible about the object under study. Furthermore, the data collection methods in this study used field observations, interviews, and documentation. Data processing and analysis techniques are carried out in three ways or stages, namely data reduction, data presentation and drawing conclusions. After the researchers conducted data analysis, it was found that in the application of Islamic business ethics in the wood furniture business, the Study on Wood Furniture Unit 1 Aimas, Sorong Regency has implemented Islamic business ethics in its business such as being honest in measurements, selling good quality goods, prohibited from using oaths, loose and generous, build good relations, orderly administration, and set prices transparently. Of the three furniture, the one that applies the most Islamic business ethics is Niqayah wood furniture where almost all of the indicators that exist he always gives the best and in accordance with his Islamic business ethics, while the Pangestu wood furniture and Rahayu wood furniture both do not apply Islamic business ethics to them. administrative order because these two furnitures do not record in the event of accounts payable, these two pieces of furniture only record for proof of payment notes that will be given to the customer. However, other Islamic business ethics have been applied in these three furniture well. The buyers are also satisfied because they get a price that is not too expensive and the goods ordered are according to their wishes and get good quality.